On the Use of Fuzzy Logic in the Propagation Prediction of Radio Waves - Medeisis, A.; Kajackas, A. (Elektronika ir Elektrotechnika, 2000)
Empirical models today very often seem to provide sufficient precision for many practical tasks of propagation prediction. Such models are also very easy to use because they do not require detailed knowledge of terrain and ground clutter. However, their application sometimes may suffer from difficulty to establish correctly the empirical parameters of the model. Therefore this paper discusses a novel approach which uses the fuzzy logic to achieve better classification of propagation conditions and hence, more precise estimation of empirical parameters of the propagation prediction models. The paper suggests several categories of fuzzy sets which may be used for better classification of coverage areas. Then, based on results of experimental research, the paper proposes certain membership functions for those fuzzy sets, followed with a particular example of applying the proposed fuzzy sets to enhance estimation of empirical parameters of the modified Okumura-Hata propagation prediction model.